2021
DOI: 10.1021/acsnano.0c07680
|View full text |Cite
|
Sign up to set email alerts
|

A Potent Cancer Vaccine Adjuvant System for Particleization of Short, Synthetic CD8+ T Cell Epitopes

Abstract: Short major histocompatibility complex (MHC) class I (MHC-I)-restricted peptides contain the minimal biochemical information to induce antigen (Ag)-specific CD8+ cytotoxic T cell responses but are generally ineffective in doing so. To address this, we developed a cobalt–porphyrin (CoPoP) liposome vaccine adjuvant system that induces rapid particleization of conventional, short synthetic MHC-I epitopes, leading to strong cellular immune responses at nanogram dosing. Along with CoPoP (to induce particle formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 52 publications
1
43
0
Order By: Relevance
“…Considering the low frequency of functional neoepitopes, multiplexing strategies are of particular importance for related vaccine approaches. 12 15 To assess how effectively multivalent immunization with CPQ would present neoepitopes and induce Ag-specific CD8 + T cells in vivo, the Nes2LR neoepitope was combined with 19 or 59 other irrelevant neoepitopes from the CT26 murine cancer cell line (peptide CT1-CT59, described in our recently published work 22 ). Peptide particles were formed by simple admixing with CPQ liposomes, and the dose for each peptide, including Nes2LR, was 150 ng for the 20-plex particle vaccine and 50 ng for the 60-plex particle vaccine, for a total peptide dose of 3 µg.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the low frequency of functional neoepitopes, multiplexing strategies are of particular importance for related vaccine approaches. 12 15 To assess how effectively multivalent immunization with CPQ would present neoepitopes and induce Ag-specific CD8 + T cells in vivo, the Nes2LR neoepitope was combined with 19 or 59 other irrelevant neoepitopes from the CT26 murine cancer cell line (peptide CT1-CT59, described in our recently published work 22 ). Peptide particles were formed by simple admixing with CPQ liposomes, and the dose for each peptide, including Nes2LR, was 150 ng for the 20-plex particle vaccine and 50 ng for the 60-plex particle vaccine, for a total peptide dose of 3 µg.…”
Section: Resultsmentioning
confidence: 99%
“…Control peptides CT1–CT59 were synthesized by Genscript, and those sequences and peptide information are described in a recently published work. 22 CoPoP was produced as previously described. 24 The lipids used were: DOPC (Corden, catalog number LP-R4-070), cholesterol (PhytoChol, Wilshire Technologies), and synthetic PHAD-3D6A (Avanti, catalog number 699855).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase the immunogenicity of the liposome formulation, the immunostimulatory adjuvants QS-21, a saponin, and PHAD, a synthetic MPLA, are incorporated. The inclusion of PHAD has been shown to increase the functional immune response of CoPoP liposomes displaying influenza virus surface proteins ( 18 ), and inclusion of QS-21 in CoPoP liposomes has been shown to enhance cellular immunity ( 19 ). We previously reported that the his-tagged RBD was able to form a stable interaction with CoPoP liposomes that, when administered into mice and rabbits, produced antigen-specific cellular responses and antibodies that potently inhibited SARS-CoV-2 replication in mammalian cells ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…[32] Certain nanostructures are valuable tools for delivering vaccine components and initiating immune responses, as they provide the opportunity to package the immune activator (adjuvant) and target (antigen) with precise structural control over the placement, orientation, and chemical connectivity of each component, resulting in synergistic immune responses. Indeed, such structures advance therapeutic development, as they allow one to both: 1) manipulate and deliver immunologically active components to target sites, [33][34][35][36][37][38][39][40] and 2) program the pharmacokinetics and codelivery of these compounds. [41][42][43][44][45][46][47] Spherical nucleic acids (SNAs) are nanoscale architectures particularly well suited for immune modulation due to their modularity, tunability, and facile synthesis from chemical building blocks.…”
Section: Introductionmentioning
confidence: 99%